See no evil the reception of pornography among male audiences in Marikina City - Chingcuanco, Franchette A.; Silpedes, Auragae M.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The subject of pornography has always been interesting and fascinating. Moralists and conservatives, however, would find it odd and inappropriate, especially in a culture where pornography is considered extremely immoral and taboo, for anyone to draw interest and fascination from such a delicate subject matter. The curiosity and appeal spawned from the subject of pornography is grounded on the fact that it is not openly discussed at home and in school, the principal centers of knowledge and learning. Although the conservative and traditional nature of Philippine society dictates that pornography, in any form or representation, is evil, filthy, unlawful, and forbidden, it has quickly and predominantly found for itself a market whose composition is made up particularly of males. This thesis regarding the subject of pornography was undertaken concerning the reception of pornography among male media audiences in Marikina City to pursue the researchers' interest and broaden their knowledge about the subject matter. Adult male informants, who considered themselves knowledgeable about pornography, were picked from among natives and residents of Marikina City. Various insights and concepts were derived from the information gathered from interviews conducted with the informants. The study found that there is a clear distinction between the presentation, theme and content of sexually related and pornographic material on television and film. According to the interviewees, because television can be accessed by everybody at anytime, it can only permit so much sexually related material and absolutely no pornography. This could be attributed to the fact that television is governed by censorship laws that protect the public and guard their morals. Film, on the other hand, contains much more materials with sexual content and pornography because taking into consideration the classification of the film assigned by the movie board, the public has the discretion to watch or not. Conceptions of socially and morally accepted sexual acts on television and film also vary from person to person. Another discovery of the study was the reasons why males perceive themselves to be the primary customers of the commodities pornography sells. Based on the interviews conducted, the first motive of males for watching pornography was to satisfy the curiosity and innocence of youth. Looking deeper, however, males deemed pornography to be an outlet for males' sexual release and reinforcement of their sexual identity. Pornography strengthened their positions in society as the active players and initiators. They consumed pornography because they see it as a source of power and strength over females. Before the study was conducted, the researchers presumed that culture alone would play a major role in the male audience reception of pornography. Towards the end of the study, however, this presumption was not completely supported because according to the informants, culture is not the sole inherent factor that may influence the male audience's reception of pornography. Rather, there are other existing factors like personal experiences and personal convictions. The researchers also found out that it is actually pornography which affects the culture because people who are exposed to it become more liberal in their thinking therefore detaching themselves from the usual mindset of their culture.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Pornography and society -- Marikina, Philippines